2005
DOI: 10.1590/s1413-81232005000400024
|View full text |Cite
|
Sign up to set email alerts
|

Perda dentária e seu significado na qualidade de vida de adultos usuários de serviço público de saúde bucal do Centro de Saúde Boa Vista, em Belo Horizonte

Abstract: Este trabalho objetivou estudar os problemas causados pela perda dentária e a falta de acesso à prótese na vida diária da população adulta, usuária de uma unidade de saúde da Secretaria Municipal de Saúde de Belo Horizonte (SMSBH). Trata-se de uma pesquisa qualitativa, realizada por meio de entrevistas abertas, semi-estruturadas, com 20 pacientes atendidos no Centro de Saúde Boa Vista, pertencente à Regional Leste. Os resultados mostraram que os problemas vivenciados pelos pacientes foram tanto funcionais quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
62

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 8 publications
3
23
0
62
Order By: Relevance
“…In the comparison between individuals with and without dentures, there was no difference regarding most of the domains of the SWAL-QOL (10 domains). This indicated that the use of dentures contributes for the maintenance of a healthy eating in the elderly, corroborating other studies about the matter (15,16) . The only domain that presented difference was "Symptoms", which investigates, among other aspects, the satisfaction regarding mastication and the oral phase of swallowing.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the comparison between individuals with and without dentures, there was no difference regarding most of the domains of the SWAL-QOL (10 domains). This indicated that the use of dentures contributes for the maintenance of a healthy eating in the elderly, corroborating other studies about the matter (15,16) . The only domain that presented difference was "Symptoms", which investigates, among other aspects, the satisfaction regarding mastication and the oral phase of swallowing.…”
Section: Discussionsupporting
confidence: 90%
“…When the adaptation is compromised, there may be: muscular and osseous instability; difficulties to speak, difficulties to chew and swallow, and decreased tasting sensation (14)(15)(16)(17) . In the present study, when the domains of the SWAL-QOL protocol were related to the adaptation of dentures (self-reported by the patient), it was possible to observe that there were differences in the domains "burden", "eating duration" and "frequency of symptoms".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vargas, Paixão 18 claim that individuals associate the absence of dental elements and oral prosthetics with digestive problems. These come from inadequate chewing and grinding of the food, consequently impairing the absorption of the nutrients and may also trigger stomach problems such as gastritis and ulcers.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of good appearance is considered a facilitating issue for the acceptance of the individual by the social group, highlighting the smile and healthy teeth asimportant symbols of presentation and appearance 18,19 .…”
Section: Resultsmentioning
confidence: 99%